In(di)visable: inquiring into being 'othered' as a means to teach social justice in PHETE. (1st November 2020) - Hennig, Lauren C.; Schaefer, Lee; Gleddie, Douglas
ABSTRACT: The goal of physical education (PE) is to increase student confidence, competence, and motivation to lead physically active lifestyles. Research has shown that physical education teacher education (PETE) students tend to be sexist, elitist and unsympathetic towards social issues. Currently, a gap in culturally responsive and socially just forms of PE that bring attention to racism, colonialism, sexism, heteronormativity, and other social issues requires greater acknowledgement from researchers. OBJECTIVES: The purpose of this study is to (1) better understand how PETE students might be engaged to take on a critical agenda that would increase their willingness to teach in culturally responsive ways, and (2) engage in more socially just forms of PE. METHODS: Using autobiographical narrative inquiry, three students confront and explain their reactions to dominant discourses that have shaped their identities and think critically about how their own experiences may be different than the students who will be in their future classes. The study uses narrative inquiry methodology to engage with the individual and shared experiences of participants. Drawing on three preservice teachers' narratives, the author illustrates how a different starting point in teacher education may enrich and shape beginning PE teachers' capacity to teach in socially just ways. RESULTS: The participant accounts challenge the work of those critics who have long assumed that critical pedagogies are most appropriate for teaching preservice teachers about matters of social justice. The finding that these preservice teachers are capable of understanding and engaging in social justice issues despite social privilege should be of interest to teacher educators because it constitutes a call for change. CONCLUSION: This method of inquiry allows for the examination of tensions and shifting identities that are lived by preservice teachers impacting their conceptions of teaching and learning.